2022
DOI: 10.1016/j.jcmgh.2021.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulating Cholangiopathy-Associated Necroptotic Cell Death In Vitro Using Human Cholangiocyte Organoids

Abstract: Background & Aims Liver and bile duct diseases often are associated with extensive cell death of cholangiocytes. Necroptosis represents a common mode of programmed cell death in cholangiopathy, however, detailed mechanistic knowledge is limited owing to the lack of appropriate in vitro models. To address this void, we investigated whether human intrahepatic cholangiocyte organoids (ICOs) can recapitulate cholangiopathy-associated necroptosis and whether this model can be used for drug screening. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…To determine whether the activation of pMLKL is involved in rat hepatic IRI, rat liver biopsies were collected after 22 hours of cold storage and 24 hours of reperfusion or sham operation ( Figure 1A ), followed by immunohistochemistry staining of pMLKL using a validated antibody ( 27 , 40 , 41 ). Compared to sham-operated rats, a significant increase of serum ALT (1153.0 (441.5-1652.0) vs 10.0 (10.0-17.5), p =0.029) and AST (1294.0 (654.5-1497.0) vs 66.5 (47.0-94.0), p =0.029) levels was observed in rats after LT ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To determine whether the activation of pMLKL is involved in rat hepatic IRI, rat liver biopsies were collected after 22 hours of cold storage and 24 hours of reperfusion or sham operation ( Figure 1A ), followed by immunohistochemistry staining of pMLKL using a validated antibody ( 27 , 40 , 41 ). Compared to sham-operated rats, a significant increase of serum ALT (1153.0 (441.5-1652.0) vs 10.0 (10.0-17.5), p =0.029) and AST (1294.0 (654.5-1497.0) vs 66.5 (47.0-94.0), p =0.029) levels was observed in rats after LT ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, apoptosis has been one of the key targets, but the translation into clinical practice has been merely lacking. Except for apoptosis, the emerging role of programmed cell death has been validated in hepatic IRI, expanding our knowledge of the different cell death programs during LT. We previously reported that most pMLKL positive cells were found in the portal triads in LT biopsies, but were absent in ischemia-free liver biopsies collected from living donors grafts, suggesting the involvement of pMLKL-mediated cell death in hepatic IRI ( 27 ). Myofibroblasts are the main effectors of liver fibrosis ( 31 ) and we concluded in this study that myofibroblasts represent a major cell type with pMLKL activation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations